Energy balance of thermal and catalytic degradation processes of plastic waste for producing alternative fuel - Sasongko, Beni Tri; Wisnu Wardhana, Prabuditya Bhisma; Kurniawan, Stephanus Danny; Susilo, Gunawan Budi (Journal of Engineering and Applied Technology, 2023)
A simple thermal and catalytic degradation of polyethylene plastic waste has been carried out to produce alternative liquid fuel. Plastic of 1500 grams was pyrolyzed at a specific temperature of 450 °C. The gases were condensed in a water-cooled condenser and collected in a liquid container. Energy balance calculation was done where catalytic cracking with Y zeolite as catalyst seemed to be the best because the generated thermal energy from waste plastic oil was already higher than the required electric energy supplied for the cracking. However, several improvements must always be made in order to save more energy and create the best result for commercialization.